Ministerial Decree No. 442/2015 Concerning the Rules Governing the Payment of the Monthly Special Raise Determined According to Law No. 99 of the Year 2015 = قرار وزاري رقم 442 لسنة 2015 بشأن قواعد صرف العلاوة الخاصة الشهرية المقررة بالقانون رقم 99 لسنة 2015 - Egypt; The middle east library for economic services, translator. (2025)
Ministry of finance decree no. 442 of the year 2015 concerning the rules governing the payment of the monthly special raise determined according to law no. 99 of the year 2015 وزارة المالية قرار رقم 442 لسنة 2015 بشأن قواعد صرف العلاوة الخاصة الشهرية المقررة بالقانون رقم 99 لسنة 2015